2015
DOI: 10.5099/aj150300156
|View full text |Cite
|
Sign up to set email alerts
|

Tetrapeptide KEDW Interacts with DNA and Regulates Gene Expression

Abstract: Peptide KEDW (Lys-Glu-Asp-Trp-NH2) is known to reduce the blood glucose level in rats with streptozotocin-and alloxan-induced diabetes mellitus. Here, we examine the influence of KEDW peptide on cell differentiation and DNA structure. KEDW peptide increased the expression of PDX1, NGN3, PAX6, FOXA2, NKX2-2, NKX6.1, and PAX4 genes but decreased MNX1 and HOXA3 gene expression when added to pancreatic cell culture. Moreover, KEDW peptide caused an increase in expression of PDX1, NGN3, PAX6, FOXA2, NKX2-2, NKX6.1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…KEDW(Lys-Glu-Asp-Trp) peptide has the ability to induce differentiation and functional activity of various types of endocrine pancreatic cells. 20…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…KEDW(Lys-Glu-Asp-Trp) peptide has the ability to induce differentiation and functional activity of various types of endocrine pancreatic cells. 20…”
Section: Introductionmentioning
confidence: 99%
“…19 KEDW(Lys-Glu-Asp-Trp) peptide has the ability to induce differentiation and functional activity of various types of endocrine pancreatic cells. 20 Thus, short peptides are involved in the regulation of proliferation and differentiation processes in various types of cells and tissues. The aim of this study was to investigate the effect of short peptides AED (Ala-Glu-Asp), KED, KE (Lys-Glu), and AEDG and also their mixtures on the initial stages of neuronal differentiation and proliferation of the primary culture of human periodontal ligament hPDLSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Results obtained through physical methods (UV-visible absorption, circular dichroism) and molecular modelling methods suggest that the peptide binds to DNA along the major groove. Experimental and theoretical data provided a 3D model of a stable DNA-peptide complex [43]. Another peptide, AEDL, regulates the levels of Ki67, Mcl-1, p53, CD79, NOS-3 proteins in cell cultures of human bronchial epithelium in various passages.…”
Section: Discussionmentioning
confidence: 99%
“…The study of the properties of the peptide KEDW by means of UV spectroscopy, circular dichroism, and molecular modeling has demonstrated that this tetrapeptide binds to the DNA in association with the sequence ACCT, which is found in the promoter regions of genes responsible for the functional state of pancreatic cells. The authors used this result to present an explanation of the previously identified properties of the tetrapeptide [42].…”
Section: Short Peptides + Dnamentioning
confidence: 98%
“…It has been demonstrated that the AEDL peptide induces the differentiation of lung cells by regulating the expression of the NKX2-1, SCGB1A1, SCGB3A2, FOXA1, and FOXA2 genes [41]. Another study showed that the peptide KEDW increases the expression of the genes PDX1, NGN3, MNX1, PAX6, FOXA2, NKX2-2, NKX6.1, HOXA3, and PAX4 that are important for maintaining the functional activity of pancreatic endocrine cells [42]. It has been established that directed differentiation of immune cells is stimulated by the peptides KE, DS, (Nα-(γ-E) -E), K (H-E-OH) -OH, AED, KED, EDA, and KEDG [34].…”
Section: Peptide Regulation Of Cell Differentiationmentioning
confidence: 99%